Risk Management Analysis in Corporate Strategic Decision Making - Gabriel Sinaga (Patua : Journal of Business Administration and Management, 2024)
This study aims to analyze the role of risk management in corporate strategic decision-making. In an uncertain business environment, the implementation of risk management is a crucial factor in improving the quality of management decisions. This study employed a quantitative approach with a descriptive and associative design. Data were collected through questionnaires distributed to 80 respondents, consisting of managers and staff involved in the strategic decision-making process. Data analysis techniques included validity and reliability tests, descriptive analysis, and linear regression using SPSS software. The results showed that risk management had a positive and significant effect on strategic decision-making, with a regression coefficient of 0.735 and a significance level of 0.000 <0.05. The coefficient of determination (R²) of 0.642 indicates that 64.2% of the variation in strategic decision-making can be explained by risk management, while the remainder is influenced by factors outside the study. This indicates that the better the implementation of risk management, the more effective and appropriate the resulting strategic decisions. Thus, this study emphasizes the importance of integrating risk management into the strategic decision-making process to improve company performance and sustainability amidst the dynamics of the business environment.